2020
DOI: 10.3390/nu12082431
|View full text |Cite
|
Sign up to set email alerts
|

Displacing Sedentary Behaviour with Light Intensity Physical Activity Spontaneously Alters Habitual Macronutrient Intake and Enhances Dietary Quality in Older Females

Abstract: Displacing Sedentary Behaviour (SB) with light intensity physical activity (LIPA) is increasingly viewed as a viable means of health enhancement. It is, however, unclear whether any behavioural compensations accompany such an intervention. Therefore, the aim of this study was to identify any dietary changes that accompany SB displacement. We hypothesised that SB displacement would improve dietary quality. Thirty-five elderly females (73 ± 5 years) were randomly allocated to one of three groups: (1) sedentary b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 75 publications
(114 reference statements)
1
23
0
Order By: Relevance
“…Title and abstract evaluation identified 79 potential manuscripts for full text screening. After screening full articles, 19 reports met all inclusion criteria (46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64). One additional article was identified via hand searching (65).…”
Section: Study Identificationmentioning
confidence: 99%
See 4 more Smart Citations
“…Title and abstract evaluation identified 79 potential manuscripts for full text screening. After screening full articles, 19 reports met all inclusion criteria (46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64). One additional article was identified via hand searching (65).…”
Section: Study Identificationmentioning
confidence: 99%
“…Reports with duplicate data from included studies were retained, however, five studies which could not be interpreted without further detail were eliminated (59,60,(62)(63)(64). Ultimately, 13 unique studies were represented by 15 reports and were included in analyses (46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)61 (61). The results of the literature search and study selection are reported as a PRISMA flow diagram in Figure 1 (37).…”
Section: Study Identificationmentioning
confidence: 99%
See 3 more Smart Citations